1999
DOI: 10.1007/s001250051115
|View full text |Cite
|
Sign up to set email alerts
|

The relation between QTc interval prolongation and diabetic complications. The EURODIAB IDDM Complication Study Group

Abstract: The QT interval reflects the total duration of ventricular myocardial depolarization and repolarization: a prolonged QT interval is associated with sudden death and poor survival in apparently healthy subjects [1]. The relation of QT interval prolongation with diabetes complications, poor survival prognosis and sudden death has recently received considerable interest. It has been postulated that QT prolongation accounts for higher mortality in people with diabetes and its complications as the prevalence of QT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
3
8

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(151 citation statements)
references
References 48 publications
11
124
3
8
Order By: Relevance
“…To our knowledge, this is the first study to prospectively assess the role of QT c and rHR in both types of diabetes within the same study framework. Its findings confirm the prognostic value of QT c as an independent risk factor for all-cause mortality in type 1 diabetes [5,[28][29][30]. In addition to the results of Rossing et al [5], the present…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To our knowledge, this is the first study to prospectively assess the role of QT c and rHR in both types of diabetes within the same study framework. Its findings confirm the prognostic value of QT c as an independent risk factor for all-cause mortality in type 1 diabetes [5,[28][29][30]. In addition to the results of Rossing et al [5], the present…”
Section: Discussionsupporting
confidence: 89%
“…The HR for overall mortality found in the present analysis was comparable to that in Rossing's report [5], but tended to be lower than the risk ratio found in subjects with overt nephropathy [28] (1.10 and 1.47 per 10 ms, respectively). Earlier reports have suggested that the association between QT c and cardiovascular disease was stronger in male than in female subjects with type 1 diabetes [30]. The present study had slightly more female subjects in the group with type 1 diabetes, thereby potentially underestimating the prognostic value of QT c for this patient group.…”
Section: Qtc Intervalcontrasting
confidence: 59%
See 2 more Smart Citations
“…13 In patients with arterial hypertension, QT interval parameters have mainly been associated with left ventricular mass (LVM), [14][15][16][17][18] although a recent report suggested that they are no better than simple electrocardiographic voltage criteria for detection of left ventricular hypertrophy (LVH). 19 In diabetic patients, QT parameters have been correlated not only with the presence of cardiac dysautonomia, 20 coronary artery disease, 21 diabetic degenerative complications 22 and microalbuminuria, 23 but also with the presence of arterial hypertension and LVH. 24 In view of these reports, we investigated in a cross-sectional design study the relationships between five QT interval parameters (maximal QT and QT c duration, and QT, QT c and number of leads-adjusted QT interval dispersion) and several clinical, electrocardiographic and 2D echocardiographic variables, with particular attention to their associations with LVM and geometric patterns, since they constitute important prognostic factors in patients with arterial hypertension.…”
Section: Introductionmentioning
confidence: 99%